Perancangan Informasi Budaya Mantra Rahasia Jawa Kuno Melalui Media Buku Ilustrasi - Ghazali, Debi Nur Muhamad; Kasmana, Kankan (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2021)
The secret mantra of ancient Java is a mantra that was secretly passed down from generation to generation until now. The recitation and procedures for practicing the mantra are very unique, therefore the secret mantra becomes the Javanese culture's speech. Because of the inherent and interrelated between the mantra and the Javanese, if it is associated with the belief of a religious mantra is an activity that leads to evil and shirk. But even so the stanzas contained in mantras are an art as well as strong customs. Secret spells good or bad depends on the spell reader itself, both in intention and intent and purpose of reciting secret spells.